Mapping Employee Development in the AI Era: A Bibliometric Study on Digital Talent Agility and Technostress - Syahrani; Dwi Wahyu Artiningsih; Aida Vitria; Ana Sofia Herawati; Teguh Wicaksono; Muhammad Zaini (Cita konsultindo, 2025)
This study explores the evolution of scholarly discourse on employee development in the context of artificial intelligence (AI), digital talent agility, and technostress. Employing a bibliometric methodology, the research analyzes 1,424 peer-reviewed articles published between 2010 and 2025, sourced from Scopus and Google Scholar. The data were processed using the PRISMA protocol and visualized through VOSviewer to produce network, overlay, density, and co-authorship maps. The keyword strategy“employee development” AND “digital talent agility” AND “technostress” ensured a thematic intersection of human resource development, psychological resilience, and digital capability.The findings reveal six thematic clusters, showing that while employee development research traditionally emphasized performance and structured training, there has been a progressive shift toward digital agility, emotional sustainability, and stress management. Overlay and density visualizations demonstrate the increasing prominence of keywords such as “technostress,” “psychological well-being,” and “learning agility” after 2020. However, network and co-authorship analyses reveal a fragmented intellectual structure, indicating that the integration of psychological and technological approaches remains underdeveloped. This fragmentation highlights a critical research gap and validates the study’s novelty.The research contributes a novel conceptual synthesis by combining Dynamic Capabilities Theory and the Transactional Model of Stress and Coping, offering a comprehensive framework for understanding how organizations and individuals can adapt in AI-driven environments. The findings provide actionable insights for researchers, HR professionals, and policymakers to design employee development strategies that promote both technical competence and psychological resilience in the digital era.